(untitled) (Research, Society and Development, 2022)
This study aims to describe the pathophysiological aspects of the tumor wound in order to provide greater clarification for the nursing team that works in the care of cancer patients with neoplastic wounds. This is a scope review or scoping review, based on the recommendations of the PRISMA guideline. The bibliographic search was carried out during the month of September 2021, through the selection of controlled and uncontrolled descriptors, in the following databases: US National Library of Medicine (PudMed), Excerpta Medica dataBASE (EMBASE), Cumulative Index to Nursing and Allied Health Literature (CINAHL) and in the Virtual Health Library/Latin American and Caribbean Literature on Health Sciences (BVS/LILACS). Articles in Portuguese, English and Spanish, published between 2016 and 2021 were included. Nine articles were selected for review. Publications were carried out between 2017 and 2020, of which most were published in Brazilian journals (55.55%), 44.44% reported level 4 evidence, followed by level 3, pointed out in 33.33% of the documents evaluated. It was found that most articles were of the type systematic review (44.44%) and observational (33.33%). The main topics addressed by the articles dealt with characteristics such as pain, exudate and odor. It is concluded that although there are recent publications, they are related to similar issues lacking broader and more complex information, thus showing that there is still much to study and improve on current knowledge related to the topic in question.